Influence of voxel size on dentinal microcrack detection by micro-CT after root canal preparation - Pinto, Jáder Camilo [UNESP]; Coaguila-Llerena, Hernán [UNESP]; Torres, Fernanda Ferrari Esteves [UNESP]; Lucas-Oliveira, Éverton; BA, Tito José Bonagam; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2021)
The aim of this study was to assess the influence of micro-computed tomography (micro-CT) voxel size on dentinal microcrack detection after root canal preparation using rotary heat-treated nickeltitanium files. Curved mesial root canals (n = 24) of mandibular molars were prepared using ProDesign Logic 30/.05 (PDL) or HyFlex EDM 25/.08 (HEDM). The specimens were scanned by micro-CT at 5 µm voxel size before and after root canal preparation. The percentage of microcracks was evaluated in images at 5, 10 and 20 µm voxel size, by two examiners at two moments. The Kappa and McNemar tests (α = 0.05) were used. The percentage of dentinal microcracks was similar before and after PDL and HEDM preparations, at 10 and 20 µm (p> 0.05). HEDM showed a higher percentage of dentinal microcracks in the middle third at 5 µm after preparation (p < 0.05). The detection of dentinal microcracks before and after instrumentation using PDL was more accurate at 5 µm than at 20 µm, in all thirds (p < 0.05). Within the limitations of this ex vivo study, as expected, the results showed that different resolutions influence the micro-CT analysis of microcracks. The highest accuracy in detecting microcracks was observed for analyses performed at 5 µm voxel size. HyFlex EDM caused even more microcracks to develop in the middle third, detectable only by visualization of images made at 5 µm voxel size.
Keywords: Dental Pulp Cavity; Dentin; Endodontics; Root Canal Preparation